Invitrogen molecular biology incorporating life technologies and ResGen brand. (Invitrogen Life Technologies, 2002)
Introduces cloning and genetic engineering, exploring the technology and social issues involved and looking toward what the future might bring as it becomes possible to duplicate even human DNA.